PENGARUH PENAMBAHAN HOT WATER TERHADAP KEHILANGAN MINYAK PADA ALAT SLUDGE CENTRIFUGE PADA STASIUN KLARIFIKASI - Afandi, Wahyu Novtrian; Youfa, Rita (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2020)
Crude Palm Oil (CPO) is a vegetable oil derived from the fruit of the oil palm plant. During the processing of palm fruit into CPO, sludge is produced as a byproduct of the oil purification process. This sludge is reprocessed in a sludge centrifuge because it still contains oil, with hot water added as a diluent to facilitate the separation between sludge and oil. The addition of hot water helps maintain the balance in separating sludge and oil. Low water content will cause the incoming feed to become thicker, making it difficult to separate the oil in the sludge centrifuge. The sludge centrifuge separates the oil in the sludge using centrifugal force. To date, the company has been adding hot water at a rate of 1.5 tons per hour, resulting in oil losses in the heavy phase ranging from 0.9% to 1%. Due to the high oil content in the sludge, a study is needed to evaluate the performance of the sludge centrifuge in processing the sludge to ensure that oil losses in the heavy phase meet company standards. The method used to analyze oil losses is extraction. The results show that increasing the amount of hot water reduces the percentage of oil losses. Additionally, the optimal oil loss percentage occurs at a hot water addition of 3 tons/hour.